(3GdJMdjd Gdcej aj GdGOGQIs - (3GHQGgje CMeO(B, (3eNdhas ((3GdQjGV(B:s (3LGeYI Gdedc SYhO(B,s, 2001)
(3JLO aj gPG GdcJGH (B: (3GdHQeLI GdNWjI , Md GdHQfGeL GdNWj HGdWQjbI GdHjGfjI ,WQjbI GdSedcS ,JMdjd THcI GdCYeGd HESJNOGe Jbhje GdHQGeL heQGLYJgG hCSdhH GdeSGQ GdMQLs
(3HjHdjhZQGajG(B: (3U(B.253s
Keywords: (3GdHQeLI GdNWjIs